Heat-related cardiorespiratory mortality: Effect modification by air pollution across 482 cities from 24 countries - Rai, Masna; Stafoggia, Massimo; de'Donato, Francesca; Scortichini, Matteo; Zafeiratou, Sofia; Vazquez Fernandez, Liliana; Zhang, Siqi; Katsouyanni, Klea; Samoli, Evangelia; Rao, Shilpa; Lavigne, Eric; Guo, Yuming; et al. (Environment international, 2023)
BACKGROUND: Evidence on the potential interactive effects of heat and ambient air pollution on cause-specific mortality is inconclusive and limited to selected locations. OBJECTIVES: We investigated the effects of heat on cardiovascular and respiratory mortality and its modification by air pollution during summer months (six consecutive hottest months) in 482 locations across 24 countries. METHODS: Location-specific daily death counts and exposure data (e.g., particulate matter with diameters ≤ 2.5 µm [PM2.5]) were obtained from 2000 to 2018. We used location-specific confounder-adjusted Quasi-Poisson regression with a tensor product between air temperature and the air pollutant. We extracted heat effects at low, medium, and high levels of pollutants, defined as the 5th, 50th, and 95th percentile of the location-specific pollutant concentrations. Country-specific and overall estimates were derived using a random-effects multilevel meta-analytical model. RESULTS: Heat was associated with increased cardiorespiratory mortality. Moreover, the heat effects were modified by elevated levels of all air pollutants in most locations, with stronger effects for respiratory than cardiovascular mortality. For example, the percent increase in respiratory mortality per increase in the 2-day average summer temperature from the 75th to the 99th percentile was 7.7% (95% Confidence Interval [CI] 7.6-7.7), 11.3% (95%CI 11.2-11.3), and 14.3% (95% CI 14.1-14.5) at low, medium, and high levels of PM2.5, respectively. Similarly, cardiovascular mortality increased by 1.6 (95%CI 1.5-1.6), 5.1 (95%CI 5.1-5.2), and 8.7 (95%CI 8.7-8.8) at low, medium, and high levels of O3, respectively. DISCUSSION: We observed considerable modification of the heat effects on cardiovascular and respiratory mortality by elevated levels of air pollutants. Therefore, mitigation measures following the new WHO Air Quality Guidelines are crucial to enhance better health and promote sustainable development.
Keywords: Respiratory Tract Diseases; Environmental Pollutants; látky znečišťující životní prostředí; pevné částice; mortalita; látky znečišťující vzduch; Air Pollution; vystavení vlivu životního prostředí; Air Pollutants; Cities; vysoká teplota; nemoci dýchací soustavy; Cardiovascular mortality; znečištění ovzduší; Environmental Exposure; Air temperature; Cardiovascular Diseases; Effect modification; Humans; Mortality; Particulate Matter; velkoměsta; Hot Temperature; Heat; Air pollution; kardiovaskulární nemoci; lidé; Respiratory mortality